ChemInform Abstract: Investigation of Physical and Electrochemical Properties of β‐TaxNb1‐xPO5 as an Electrode Material for Lithium Batteries. Issue 30 (7th July 2016) - Lu, Matthew Y.; Badway, Fadwa; Kim, Joshua R.; Amatucci, Glenn G.
Abstract: In order to improve the cycling stability of β‐NbPO5 due to the avoidance of lower voltage irreversible structural transitions, at least 5% Ta 5+ is incorporated in β‐NbPO5 .